Musculoskeletal ultrasound imaging in the diagnosis of psoriatic arthritis: from the past to the future. (February 2015) - Sedie, Andrea Delle; Riente, Lucrezia
Ultrasound (US) is a reliable imaging technique that has played a key role in the imaging process in rheumatology, in recent years, for the early detection and careful characterization of the inflammatory process in arthritides. Its use in psoriatic arthritis (PsA) has become common in both clinical and research fields, focusing on joints and tendons, entheses (which have been shown to be involved not only in patients with PsA but also in subjects presenting only skin psoriasis) and some new fields (skin and nails). US allows a more precise and earlier diagnosis and therapy monitoring. There are also some new hypotheses that US could be used to discriminate between different arthritis and also between PsA and the other spondyloarthritides.